READING THE HOLY BOOKS OF CHINA - Frank Podgorski (Journal of Dharma, 1978)
Part of the uniqueness of Man is his struggle to understand; indefatigably he attempts to master the art of reading. The Book of Nature is the first text to be deciphered. Although all are heirs to this rich legacy, not all learn to read adequately. Both by extending outwardly and by probing inwardly. Man exerts his energies to discover who he is, where he is, and in what direction he and his world are heading. Man's ability to read this Book depends to a la"ge extent on his talents, his proximate environment, and his dedicated use of these. All men of all cultures share this Book of Nature; some learn: to read it better than others. Yet this Book of Nature is the initial revelation which is the common heritage of all. Characteristic of the human endeavour are efforts to read this Book with understanding, to fathom its deepest meaning.